O‐GlcNAc Engineering on a Target Protein in Cells with Nanobody‐OGT and Nanobody‐splitOGA. Issue 5 (5th May 2021) - Ramirez, Daniel H.; Ge, Yun; Woo, Christina M.
Abstract: The monosaccharide O‐linked N‐acetyl glucosamine (O‐GlcNAc) is an essential and dynamic post‐translational modification (PTM) that decorates thousands of nucleocytoplasmic proteins. Interrogating the role of O‐GlcNAc on a target protein is crucial yet challenging to perform in cells. We recently reported a pair of methods to selectively install or remove O‐GlcNAc on a target protein in cells using an engineered O‐GlcNAc transferase (OGT) or split O‐GlcNAcase (OGA) fused to a nanobody. Target protein O‐GlcNAcylation and de‐O‐GlcNAcylation complements methods to interrogate the role of O‐GlcNAc on a global scale or at individual glycosites. Herein, we describe a protocol for utilizing the nanobody‐OGT and nanobody‐splitOGA systems to screen for O‐GlcNAc functionality on a target protein. We additionally include associated protocols for the detection of O‐GlcNAc and cloning procedures to adapt the method for the user's target protein of interest. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Target protein O‐GlcNAcylation of JunB using nanobody‐OGT Basic Protocol 2 : Target protein deglycosylation of Nup62 using nanobody‐splitOGA Alternate Protocol : Verification of the O‐GlcNAc state of a tagged target protein through chemoenzymatic labeling Support Protocol : Cloning of new nanobody‐OGT/nanobody‐splitOGA and target protein pairs